PARALEGALS AND HUMANITARIAN RESPONSIBILITIES IN ADVOCATING SURVIVORS OF THE MOST SERIOUS CRIMES: LEARNING FROM WOMEN VOLUNTEERS FOR HUMANITY IN NORTH ACEH DISTRICT - Fadhil, Moh. (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
The most serious crimes that occurred in North Aceh left a deep scar for the victims. The birth of impunity causes victims to be naturally forced to survive. However, various fundamental rights that are difficult to access are a significant problem for survivors due to post-conflict trauma, making it difficult for survivors to open up to the local government. Therefore, the Women Volunteer Advocacy Institute for Humanity (RPuK) is here to bridge the fundamental rights needs of survivors with advocacy to local governments. This study aimed to determine the existence of RPuK in accommodating the fundamental rights of survivors. The method used is empirical legal research with interview and observation techniques. The study results reveal that the existence of RPuK for ten years in North Aceh Regency has built a unique advocacy program with the Regional Government in terms of fulfilling integrated service programs and unique service bazaars for survivors of the most serious crimes. Both programs focus on making identity cards, health insurance cards, marriage certificates, service mental health, employment assistance, and other fundamental rights. This success is a form of reparations as part of the fulfillment of transitional justice to the survivors. Interestingly, RPuK made a breakthrough in its food security advocacy program for the survivors during the pandemic. Thus, RPuK sees a new perspective that is far more important, prioritizing the survivors during the pandemic, fulfilling the survivors’ economic, social, and cultural rights to fulfill human rights and transitional justice.